2008
DOI: 10.1038/nnano.2008.237
|View full text |Cite
|
Sign up to set email alerts
|

Molecular junctions based on aromatic coupling

Abstract: If individual molecules are to be used as building blocks for electronic devices, it will be essential to understand charge transport at the level of single molecules. Most existing experiments rely on the synthesis of functional rod-like molecules with chemical linker groups at both ends to provide strong, covalent anchoring to the source and drain contacts. This approach has proved very successful, providing quantitative measures of single-molecule conductance, and demonstrating rectification and switching a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
344
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(384 citation statements)
references
References 48 publications
30
344
4
Order By: Relevance
“…21 Moreover, the energy level of the HOMO of conjugated molecules aligns more favorably with the Fermi level of the metal, than does that for aliphatic molecules, and results in lower tunneling barriers. 16,21,37,38 RESULTS AND DISCUSSION these values agree with previous experimental reports using single-molecule and large-area junctions. 27,[38][39][40][41][42][43][44][45] These results presented here also agree with theoretical calculations by Ratner and coworkers; these authors predict (using density functional theory, DFT) a value of  = ~0.3 Å -1 for SAMs of polyphenyldithiolates by assuming a continuous conjugation of the molecules with the metal electrodes.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…21 Moreover, the energy level of the HOMO of conjugated molecules aligns more favorably with the Fermi level of the metal, than does that for aliphatic molecules, and results in lower tunneling barriers. 16,21,37,38 RESULTS AND DISCUSSION these values agree with previous experimental reports using single-molecule and large-area junctions. 27,[38][39][40][41][42][43][44][45] These results presented here also agree with theoretical calculations by Ratner and coworkers; these authors predict (using density functional theory, DFT) a value of  = ~0.3 Å -1 for SAMs of polyphenyldithiolates by assuming a continuous conjugation of the molecules with the metal electrodes.…”
Section: Introductionsupporting
confidence: 92%
“…1 Among the exceptions are the observation of a small "odd-even effect" in charge transport across n-alkanethiolates on gold, [2][3][4] the observation of a substantial reduction in current density when fluorine is present at the SAM//Ga 2 O 3 interface, 5 and the observation of rectification of current when T is a redox active group such as ferrocenyl [6][7][8] or bipyridyl. 9 Having studied the influence of the structure of saturated n-alkyl groups on charge tunneling extensively, [10][11][12][13][14][15] we turned our attention to understanding the relationship between the structure of polyaromatics (molecules that result in a reduction in the height of the tunneling barrier relative to that characterizing aliphatics 16 ) and the rates of charge transport. We measured rates of charge transport across SAMs of oligophenylthiols (M/SPh n ), -methanethiols (M/SCH 2 Ph n ), and -acetylenes (M/C≡CPh n ), where n = 1-3 and M = gold and silver metal electrodes ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…For every log(G/G 0 ) versus Dz stretching trace, we determine the relative electrode displacement at the end of the high-conductance plateau, Dz H , which is the largest Dz value within the range À 0.34log(G/G 0 )4log ( Table 1, the JFP approaches 100% for molecules p-p-p, p-m-p, m-p-m and m-m-m. For molecule o-p-o, the JFP decreased sharply to 21% (MCBJ)/27% (STM-BJ) because the N in the terminal ortho pyridyl is partially hidden from the electrode surfaces and therefore it is difficult to form a bridge between the two gold electrodes 40 . Our inability to measure the conductance of o-m-o is explained by its short N---N length and the expected low conductance, which falls below the direct tunnelling conductance (Supplementary Note 3 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is an important consideration as for certain classes of -conjugated molecules, for instance oligo(phenylene)ethynylene (OPE) derivatives, it has been shown that proximal molecular bridges can -stack in molecular electrical junctions and can, on occasions, give rise to additional complications in the conductance signatures of such compounds. 20,46 11…”
Section: Resultsmentioning
confidence: 99%